THE ROLE OF ARTIFICIAL INTELLIGENCE IN ENHANCING ENGLISH LANGUAGE LEARNING: OPPORTUNITIES, CHALLENGES, AND FUTURE PERSPECTIVES - Ibodova Shahzoda Mirsalim qizi,; Sagatova Muborak Payzidinovna, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract The  rapid  development  of  Artificial  Intelligence  (AI)  has  significantly transformed educational systems around the world. One of the areas most influenced by this technological advancement is foreign language education, particularly English language  learning.  As  English  has  become  the  dominant  language  of  international communication,  science,  technology,  media,  and  global  business,  the  demand  for effective  and  accessible  learning  methods  has  increased  considerably.  Traditional teaching  approaches  often  encounter  limitations,  including  insufficient  individual attention, restricted opportunities for authentic communication, and unequal access to educational resources. Artificial Intelligence has emerged as an innovative solution to these  challenges  by  introducing  intelligent  tutoring  systems,  adaptive  learning platforms, speech recognition software, and conversational agents.